2018
DOI: 10.1186/s13148-018-0574-0
|View full text |Cite
|
Sign up to set email alerts
|

A five-DNA methylation signature act as a novel prognostic biomarker in patients with ovarian serous cystadenocarcinoma

Abstract: BackgroundOvarian cancer is the most fatal tumor of the female reproductive system and the fifth leading cause of cancer death among women in the USA. The prognosis is poor due to the lack of biomarkers for treatment options.ResultsThe methylation array data of 551 patients with ovarian serous cystadenocarcinoma (OSC) in The Cancer Genome Atlas (TCGA) database were assessed in this study to explore the methylation biomarkers associated with prognosis and improve the prognosis of patients. These patients were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…DNA methylation profiling is a recent method that has been used to improve tumor classification, and this technique has already led to re-definitions and sub-classifications of various tumors such as glioblastoma (Noushmehr et al, 2010), head and neck squamous carcinoma (Brennan et al, 2017), adrenocortical carcinoma (Barreau et al, 2013), and hepatocellular carcinoma (Li et al, 2019). Furthermore, several prognostic signatures based on DNA methylation sites have been reported to stratify the prognosis of various cancers such as cutaneous melanoma (Guo et al, 2019), ovarian cancer (Guo et al, 2018), lung adenocarcinoma (Wang et al, 2019a), and breast cancer (Tao et al, 2019). These studies support that DNA methylation sites can serve as promising biomarkers for subtype identification and prognostic stratification in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation profiling is a recent method that has been used to improve tumor classification, and this technique has already led to re-definitions and sub-classifications of various tumors such as glioblastoma (Noushmehr et al, 2010), head and neck squamous carcinoma (Brennan et al, 2017), adrenocortical carcinoma (Barreau et al, 2013), and hepatocellular carcinoma (Li et al, 2019). Furthermore, several prognostic signatures based on DNA methylation sites have been reported to stratify the prognosis of various cancers such as cutaneous melanoma (Guo et al, 2019), ovarian cancer (Guo et al, 2018), lung adenocarcinoma (Wang et al, 2019a), and breast cancer (Tao et al, 2019). These studies support that DNA methylation sites can serve as promising biomarkers for subtype identification and prognostic stratification in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the expression of p16 INK4a protein has been reported as a progression/regression tumor marker in LSIL cervix lesions [38,39]. Other studies reported that combinations including a five-DNA methylation panel [40], a circulating miRNA panel [12], a serum miRNA and CA125 panel [41], and CPG island methylation [38] are of great significance in tumor diagnostic efficacy, prognosis, surgical guidance, and epigenetic therapy. In our study, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation of NKD1, RUNX3, and ZNF671 were reported to be predictors of progression-free survival (PFS) in patients with OC [9][10][11]. Furthermore, a previous study reported that a DNA methylation signature can predict overall survival in patients with OC [12]. However, the study did not explore the correlation between DNA methylation status and PFS in OC.…”
Section: Introductionmentioning
confidence: 98%